Prospective Primary School Teachers’ Understanding of Model Representation: The Case of Static Electricity - Rifat Shafwatul Anam; Rendi Restiana Sukardi; Monika Handayani; Roseleena Anantanukulwong; Titiyaka Jajuri (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aimed to assess the comprehension levels of prospective primary school teachers regarding verbal and visual representation models of static electricity. A survey was conducted involving 110 prospective teachers from West Java Province, selected through purposive sampling. Participants were categorized based on their secondary school study programs and gender. The study utilized a five-tier test as the instrument for data collection, with responses analyzed using descriptive statistics. Verbal and visual responses were categorized into several levels. Analysis revealed that the majority of both verbal and visual responses fell into the lack of knowledge, misconception, unidentified categories. These findings highlight the inadequate understanding of static electricity concepts among prospective primary school teachers, which may contribute to students' difficulties. Differences in educational background and gender did not significantly influence the comprehension levels in either verbal or visual representations of static electricity concepts. This provides insight into the fact that the topic of static electricity, though often regarded as straightforward and revisited at various educational stages from primary to secondary school, remains a source of widespread misunderstanding and error. The study underscores the critical need for targeted interventions in teacher education programs to enhance understanding and effective teaching of scientific concepts like static electricity at the primary school level.